2019
DOI: 10.1161/circresaha.119.315243
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics Reveals Chemotaxis-Mediated Intraorgan Crosstalk During Cardiogenesis

Abstract: Rationale: We hypothesized that the differentiation processes of cardiac progenitor cell (CP) from first and second heart fields (FHF and SHF) may undergo the unique instructive gene regulatory networks or signaling pathways, and the precise SHF progression is contingent on the FHF signaling developmental cues. Objective: We investigated how the intraorgan communications control sequential building of discrete an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 56 publications
1
43
0
Order By: Relevance
“…There has been tremendous effort to study the developing embryonic cardiovascular system to gain insight into the factors associated with cardiac regeneration. Single-cell resolution has allowed us to obtain a far more detailed and more complete picture of cellular transitions during development (66,67). scRNA-seq has been utilized to better understand the complex genetic regulatory and epigenetic networking of various stages of multipotent stem cell differentiation during heart development.…”
Section: Implementation Of Scrna-seq In Regenerative Cardiologymentioning
confidence: 99%
“…There has been tremendous effort to study the developing embryonic cardiovascular system to gain insight into the factors associated with cardiac regeneration. Single-cell resolution has allowed us to obtain a far more detailed and more complete picture of cellular transitions during development (66,67). scRNA-seq has been utilized to better understand the complex genetic regulatory and epigenetic networking of various stages of multipotent stem cell differentiation during heart development.…”
Section: Implementation Of Scrna-seq In Regenerative Cardiologymentioning
confidence: 99%
“…Collectively, our data support the model that HVPs expressing CXCR4 sense CXCL12 secreted by CFs at the injury site as a chemoattracting signal to repopulate the damaged myocardial compartment. A similar, chemokine-controlled deployment of SHF cells has been identified as intra-organ crosstalk between progenitors and FHF CMs during mouse cardiogenesis 36 , suggesting that migration programs that are functional during cardiac development are re-activated in HVPs during organ regeneration.…”
Section: Chemotaxis Of Hvps To Sites Of Cardiac Injury Is Mediated Bymentioning
confidence: 65%
“…They revealed spatiotemporal transcriptomic changes during heart development and showed that Nkx2-5 is an important factor in CM maturation. Xiong et al utilized FACS and revealed that Nkx2-5 directly regulates spatial expression of the chemokine receptors Cxcr2 and Cxcr4 in the second heart field, which directs second heart field cardiac progenitor migration with spatiotemporal precision [9]. In addition to Nkx2-5, Mesp1 is also essential for CM maturation.…”
Section: Murine Embryonic and Neonatal Heartmentioning
confidence: 99%
“…Velocyto is a package for the analysis of expression dynamics from the estimation of RNA velocities by distinguishing unspliced and spliced mRNAs [56]. They have been used in studies of cardiac development and disease progression [9,11,14,[21][22][23]32,36,38].…”
Section: Spatial Transcriptomesmentioning
confidence: 99%